Budaya Sekolah Terhadap Perkembangan Kepribadian Peserta Didik Di SMA Negeri 3 Bantaeng - Inayah Zalzabila Sam; Pajri Pajri; Mauliana Mauliana; Rahma Dani; Ghina Firzana Fadly (PT. Citra Media Publishing, 2025)
School culture is a system of values, beliefs, and habits that exist within the educational environment and function as a guideline for the behavior of all school members. A good school culture can create a conducive learning atmosphere, motivate students, and foster positive personalities that support educational success. This study aims to analyze the influence of school culture on the personality development of students at SMAN 3 Bantaeng. The approach used is qualitative with a descriptive method. Data were collected through observation, interviews, and documentation studies involving teachers and students. The results of the study show that the school culture at SMAN 3 Bantaeng such as the culture of discipline, religiosity, cooperation, and responsibility contributes significantly to shaping students’ personalities. These values are internalized through regular school activities, habitual practices, and teachers’ role modeling. Such positive culture helps improve students’ sense of responsibility, respectfulness, and learning motivation. Thus, it can be concluded that school culture has a real and meaningful influence on students’ personality development, both in moral, social, and spiritual aspects